Placental vitamin D receptor (VDR) expression is related to neonatal vitamin D status, placental calcium transfer, and fetal bone length in pregnant adolescents. Issue 5 (20th February 2014) - Young, Bridget E.; Cooper, Elizabeth M.; McIntyre, Allison W.; Kent, Tera; Witter, Frank; Harris, Z. Leah; O'Brien, Kimberly O.
ABSTRACT: The purpose of the study was to identify determinants of placental vitamin D receptor (VDR) expression and placental calcium (Ca) transfer among pregnant adolescents. Placental tissue was obtained in 94 adolescents (≤18 yr) at term. In 12 of these teens, stable Ca isotopes were given intravenously ( 42 Ca) and orally ( 44 Ca) early in labor. Placental VDR expression was assessed via Western blot and validated by RT‐PCR Maternal‐to‐fetal Ca transfer was calculated as the enrichment in cord blood at delivery relative to maternal serum enrichment 2 h postdosing. Isotopic study outcomes were examined in relation to fetal long bone length, placental VDR, serum 25‐hydroxyvitamin D [25(OH)D], 1, 25‐dihydroxyvitamin D [1, 25(OH)2 D], and parathyroid hormone (PTH) in maternal circulation and cord blood at delivery. Placental VDR expression was inversely associated with neonatal 25(OH)D ( P =0.012) and positively with neonatal 1, 25(OH)2 D ( P =0.006). Placental VDR was a positive predictor of fetal femur length Z score ( P =0.018; R 2 =0.06) and was positively correlated with maternal‐to‐fetal transfer of intravenous 42 Ca ( P =0.004; R 2 =0.62). The fetus may regulate placental VDR expression given the significant associations with neonatal vitamin D metabolites. The association between placental VDR and fetal long bone length may indicate a role for VDR in fetal bone development, potentially by mediating transplacental Ca transfer.—Young, B. E., Cooper, E. M., McIntyre, A. W., Kent, T., Witter, F., Harris, Z. L., O'Brien, K. O. Placental vitamin D receptor (VDR) expression is related to neonatal vitamin D status, placental calcium transfer, and fetal bone length in pregnant adolescents. FASEB J . 28, 2029–2037 (2014). www.fasebj.org